Redefining CRP in tissue injury and repair: more than an acute pro-inflammatory mediator - Potempa, Marc; Hart, Peter C.; Rajab, Ibraheem M.; Potempa, Lawrence A. (Frontiers in Immunology, 2025)
Most early studies investigating the role of C-reactive protein (CRP) in tissue damage determined it supported pro-hemostatic and pro-inflammatory activities. However, these findings were not universal, as other data suggested CRP inhibited these same processes. A potential explanation for these disparate observations finally emerged with the recognition that CRP undergoes context-dependent conformational changes in vivo, and each of its three isoforms – pentameric CRP (pCRP), modified pentameric CRP (pCRP*), and monomeric CRP (mCRP) – have different effects. In this review, we consider this new paradigm and re-evaluate the role of CRP and its isoforms in the tissue repair process. Indeed, a growing body of evidence points toward the involvement of CRP not just in hemostasis and inflammation, but also in the resolution of inflammation and in tissue regeneration. Additionally, we briefly discuss the shortcomings of the currently available diagnostic tests for CRP and highlight the need for change in how CRP is currently utilized in clinical practice.